PENGARUH RANGKAP JABATAN TERHADAP EFEKTIVITAS KINERJA P2K3 DALAM UPAYA PENINGKATAN KESELAMATAN DAN KESEHATAN KERJA DI PT X - Listritika Sinaga; Bina Kurniawan; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2019)
The study of the The Impact Of Dual Positions On The Effectiveness Of P2K3 Performance In Effort To Improve Occupational Safety And Health In PT X is motivated by human resources who are having a double job in OSH, the members who are in P2K3 are not experts in the OSH field. This research was conducted with qualitative research methods, by an inductive approach method and  descriptive. This research was conducted at PT X Semarang which is engaged in electricity. The informants were selected using purposive sampling and to test the quality of the data triangulation techniques were used. The theoretical basis used in this study refers to the Peraturan Menteri Tenaga Kerja  dan Transmigrasi Nomor 4 Tahun 1987 concerning P2K3. The purpose of this study was to obtain more in-depth information regarding the effect of multiple occupations on the effectiveness of P2K3 performance in an effort to improve Occupational Safety and Health at PT X which includes P2K3 perceptions, availability of resources establishment of P2K3 organization, P2K3 job description and reporting, evaluation and monitoring of P2K3 activities. P2K3 performance at PT X has not been effective, seen from the effectiveness of P2K3 in the absence of an agenda for each P2K3 meeting at PT X, the arrangement of P2K3 management does not involve labor unions, the role of P2K3 members in management has not made OSH a priority seen from the absence at the meeting of P2K3 every month and the role of company leaders have not been active in providing OSH issues. The researcher suggested that PT X take the selections of P2K3 members into consideration in order to run the P2K3 effectively.